Reasons for the Increase in the Percentage of Divorce and Judicial Distinctions in the World and Kurdistan Region/Iraq - Khudhur Qader, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Currently, the world is going through such a period that the idea of marriage is not a big factor. Undoubtedly the oldest and most enduring institution in society is marriage and family. People have been grouping themselves into families since the beginning of human life to find social, physical, and cultural support. However, occasionally family life is such a trap because of certain circumstances. Being alone is indeed better than getting someone who leaves you miserable. Divorce comes here; it might sound simple, but agreeing to end a marriage is not easy for a husband and wife. They also spend a long time trying to settle the problems before agreeing to divorce. Further, often they simply cannot solve the issues, and they agree that the only option is a divorce. Transition is a normal part of life, but sometimes it is very hard to cope with when it happens to your family. This paper will address the definition and religious aspects of marriage and then divorce in terms of the world and Kurdistan region context with the aid of the secondary data, exploring the causes of growing divorce rates.